PENGARUH PERGANTIAN AUDITOR, AUDIT TENUR, DAN FINANCIAL DISTRESS TERHADAP KETERLAMBATAN LAPORAN AUDIT - Khamaini, Ryan Achmad; Astuti, Christina Dwi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2026)
This study aims to examine the effect of auditor turnover, audit tenure, and financial distress on audit report lag. Audit report lag is an important indicator of the timeliness of financial reporting, which affects the quality of information for stakeholders. This study uses a quantitative approach with secondary data in the form of annual financial reports of non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The research sample was determined using purposive sampling. The analysis method used is panel data regression. The results show that audit tenure has a negative effect on audit report lag, while auditor turnover and financial distress have no effect on audit report lag.